To find the equation that represents the function described by the table, we can look for a linear relationship between \(x\) and \(y\).
The values from the table are:
\[ \begin{align*} x & : 0 & y & : -5 \ 1 & : -9 \ 2 & : -13 \ 3 & : -17 \ \end{align*} \]
First, we can identify how \(y\) changes as \(x\) increases:
- From \(x = 0\) to \(x = 1\), \(y\) changes from \(-5\) to \(-9\) (a change of \(-4\)).
- From \(x = 1\) to \(x = 2\), \(y\) changes from \(-9\) to \(-13\) (a change of \(-4\)).
- From \(x = 2\) to \(x = 3\), \(y\) changes from \(-13\) to \(-17\) (a change of \(-4\)).
This shows that for every increase of \(x\) by 1, \(y\) decreases by 4. This gives us a slope of \(-4\).
Next, we can use the slope-intercept form of a linear equation, which is
\[ y = mx + b \]
where \(m\) is the slope and \(b\) is the y-intercept. We can determine \(b\) by substituting one of the points into the equation.
Using the point \( (0, -5) \):
\[ -5 = -4(0) + b \implies b = -5. \]
So, the equation that describes the relationship between \(x\) and \(y\) is:
\[ y = -4x - 5. \]
In function notation, this can be written as:
\[ f(x) = -4x - 5. \]
Now, looking at the options provided, the correct answer is:
f(x) = -4x - 5.